Prophetic Traditions Regarding Enticement And Intimidation In Uniting The Nation: An Analytical Study - Mesbahul Hoque; Amran Bin Abdul Halim; Ahmad Sanusi Bin Azmi; Muneer Ali Abdul Rab (USIM Press, 2024)
There are a lot of hadith were narrated from the Prophet (S.A) that emphasize the factors of the unity of the Ummah and desire it and warn strongly about the separation and fragmentation in the Ummah. This paper aims to study and analyze some of those hadiths, by using descriptive and analytical approach. Result of this study shows that the Messengers of Allah was very concern for the unity of Ummah as his concern for Iman, Out of his concern for the unity of Ummah he established the pillars of unity in the Ummah, and chose a policy of enticement and intimidation towards those who separate the Ummah and disperse its unity.